2020
DOI: 10.1007/s00360-020-01306-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic mercury on Mytilus galloprovincialis hemocyte function and morphology

Abstract: Filter-feeding organisms accumulate xenobiotics and other substances in their tissues. They can be useful as sentinel organisms in biomonitoring of the marine compartment. Bivalve cellular immunity is ensured by phagocytosis and cytotoxic reactions carried out by hemocytes in a network with humoral responses. These can be affected by chemical contaminants in water that can be immunosuppressors also at a low concentration increasing the sensibility to pathogens. This work is an attempt to individuate cellular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 80 publications
0
9
0
1
Order By: Relevance
“…Fish are usually exposed to MeHg through their feed (fish meal) and environmental water pollution [ 20 ]. The direct and indirect exposure of MeHg by fish can cause loss of appetite, brain damage, abnormal system development, cell necrosis, and the inhibition of respiratory burst activity, all of which affect the growth and immune response of fish and shellfish [ 21 , 22 , 23 , 24 ]. In this study, we evaluated data regarding the effect of MeHg exposure on nonspecific immune response and bioaccumulation in hybrid grouper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish are usually exposed to MeHg through their feed (fish meal) and environmental water pollution [ 20 ]. The direct and indirect exposure of MeHg by fish can cause loss of appetite, brain damage, abnormal system development, cell necrosis, and the inhibition of respiratory burst activity, all of which affect the growth and immune response of fish and shellfish [ 21 , 22 , 23 , 24 ]. In this study, we evaluated data regarding the effect of MeHg exposure on nonspecific immune response and bioaccumulation in hybrid grouper.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro approaches are used to observe the effects of MeHg exposure, particularly on nonspecific immune responses of aquatic species including phagocytic activity and O 2 − production rate. A relevant study demonstrated that Mediterranean mussel ( Mytilus galloprovincialis ) hemocytes incubated with 10 −7 , 10 −6 , or 10 −5 M of MeHg had phagocytic rates that decreased with the increase of MeHg concentration and resulted in cell death [ 24 ]. Moreover, European sea bass ( Dicentrarchus labrax ) head kidney leukocytes that were incubated in 0.0005, 0.005, 0.05, or 0.1 mM of MeHg had phagocytic rates and respiratory burst activity that were significantly lower than those of that study’s control group ( p < 0.05) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Signal transduction protein, enzymes, AMPs (general and species-specific) Lysenin/Fetidin [141,170,192] CCF [181,244] mytilin, myticin, EPp [176,200] [231]…”
Section: Circulating Protein Genesmentioning
confidence: 99%
“…In some models, cell viability may also be studied by measuring metabolic activity through cell-permeable fluorescent reduction such as CTB or the colorimetric MTT. In some models the use of counter stain dye such as trypan blue or nigrosine [141,192] or the use of DNA-binding florescent dyes are alternative methods for assessing cell viability [150]. There are several methods available to measure the number of cells that are in the process of dying (apoptosis).…”
Section: Whole Cell Responsementioning
confidence: 99%
“…Lysosomes are intracellular organelle containing various hydrolytic enzymes associated with endogenous macromolecules and chemicals catabolism and metals sequestration (Moore et al,2007). Lysosomal membrane is target of several environmental stress that provoke diminution of its integrity (Shaw et al, 2019;Parisi et al, 2021). Therefore, its usefulness in several biomonitoring exercises explained by its none destructive biomarker aspect and easeful measurement by the neutral red retention time assay (NRRT) (Lowe and Pipe, 1994).…”
Section: Lysosomal Membrane Stability Assessment: Subcellular Biomarker Of Toxicitymentioning
confidence: 99%